The Effect of Different Levels of Impulsivity on Learning of Sport Skills in Open and Closed Environments - Mohamad Hosein Ghahramani; Mehdi Sohrabi; Alireza Saberi Kakhki; Mohamad Ali Besharat (University of Tehran, 2018)
The main aim of this study was to investigate the effect of different levels of impulsivity on learning of skills in open and closed environments. Participations were forty-eight male with 10 to 12 years old that signed in low impulsivity, med impulsivity, high impulsivity and control groups (combined group) in accordance to the distribution of impulsivity scores. Before and after basketball skills training program, Harrison's basketball shooting test was used to evaluation of performance and learning of skills in open and closed environments during pre-test, post-test, retention and transfer test. The results showed a significantly differences between groups for attentional functions (p=0.0001). The results of post-test and retention showed advanced performance in open environment with the increased levels of impulsivity (p=0.003). While about closed environment, progressive performance was aligned with Low levels of impulsivity groups (F=0.001). But in the transfer tests, differences between the groups were not significant (F=0.09), that was performed under the competitive goal condition. It is possible that impulsivity has a facilitator and an attenuator role in learning of various sportive skills, perhaps in open and closed environments.